Open the door how to excite young people about poetry - Lasky, Dorothea 1978-; Luxford, Dominic; Nathan, Jesse (San Francisco Poetry Foundation, 2013)
This mixture of essays, interviews, and lesson plans will prove useful for first-time and veteran teachers, parents, MFA graduates and the like, with an interest in poetry's place in the lives of our younger citizens.
Introduction : opening the door / Dominic Luxford -- pt. 1. Essays : -- The read-aloud handbook / Jim Trelease -- Poetry is an egg with a horse inside / Matthea Harvey -- The process of opening gifts / Jack Collom -- Life as primary text / James Kass -- Teaching children to write poetry / Kenneth Koch -- The care and feeding of a child's imagination / Ron Padgett -- First class / Theodore Roethke -- Children's poetry / Eileen Myles -- The change agents / Phillip Lopate -- Recitation, imitation, stillness / Jesse Nathan -- Fears, truths, and waking life / Jordan Davis -- The door called poetry / William Stafford -- Making the rounds / Jimmy Santiago Baca -- Radical strategies / Karen Volkman -- A dream / Dorothea Lasky -- pt. 2. Roundtable discussion -- Featuring leaders of poetry organizations for kids from around the United States / Dave Eggers ... [et al.] -- pt. 3. Lesson plans -- Dream machine / Michael Dickman -- Attending the living word/world / Elizabeth Bradfield -- Eavesdropping on a figure at work / Yusef Komunyakaa -- Syllabus / Meghan and Liam O'Rourke -- Three imaginary soundtracks / Eric Baus -- A perfect creature in the imperfect world / Valzhyna Mort -- Poems are for everybody / Alex Dimitrov -- Cartogram / Anthony McCann -- The image list / Michael McGriff -- Elsewhere / Katie Ford -- Bad titles / Matthew Zapruder -- Street sonnets / Deborah Landau -- Autobiographia litter-aria / Christina Davis -- Putting two and two together / Dara Wier -- Dreaming in detail / Travis Nichols -- Be a bunch of yous / Laura Solomon -- (Soma)tic poetry exercises / CAConrad -- Eating couplets and haiku / Vicki Vâertiz -- The sonnet as a silver marrow spoon / Adam O'Riordan -- Verse journalism / Quraysh Ali Lansana and Georgia A. Popoff -- Persona poetry / Quraysh Ali Lansana and Georgia A. Popoff -- A poetry of perception / Rebecca Lindenberg -- Poetry walk / Harriet Levin -- Love is the universe / Emilie Coulson -- Advice for teachers / Stephen Burt -- Afterword : a call to action (or what to do after reading this book).
Copublication with McSweeney's Books.
"Harriet Monroe Poetry Institute "Poets in the world" series editor Ilya Kaminsky."--Title page.
Includes bibliographical references.
Keywords: Poetry -- Authorship; Poetry -- Study and teaching; Poetics; Poetry and children